Fungal Spoilage and Water Adsorption Isotherm of Compound Poultry Feed - Abdullah, Noorlidah; S, Marlizan (Malaysian Journal of Science, 2004)
Water activity (A_w) or equilibrium moisture content of foodstuff is one of the environmental factors influencing growth of fungi. Among the compound poultry feed studied, mash form has the highest moisture content of 13.12% ± 0.62 corresponding to 0.88 A_w, followed by crumble form with a moisture content of 11.57% ± 0.63 corresponding to 0.87 A_w and pellet form having a moisture content of 10.84% ± 0.43 corresponding to 0.86 A_w. From the water adsorption isotherms, taking 0.65 A_w as a safe storage, the critical moisture content of mash, crumble and pellet forms of compound poultry feed were found to be 4.9%, 4.5% and 4.2% respectively. This indicates that the moisture content of all forms of compound poultry feed when sampled were above the critical value for safe storage. The spoilage of all forms of compound poultry feed determined at high water activities, ranging from 0.67-0.96 A_w at 30°C showed that compound poultry sold will have a shelf-life of 2 days at 0.96 A_w, 3-4 days at 0.88 A_w, 5-7 days at 0.82 A_w and 9-10 days at 0.75 A_w and 11-12 days at 0.67 A_w. Poultry feed in the forms of crumble and pellet gave better shelf life compared to mash form.